2017
DOI: 10.1159/000486903
|View full text |Cite
|
Sign up to set email alerts
|

A Twelve-Week Moderate Exercise Programme Improved Symptoms of Depression, Insomnia, and Verbal Learning in Post-Aneurysmal Subarachnoid Haemorrhage Patients: A Comparison with Meningioma Patients and Healthy Controls

Abstract: Objectives: Deficits in psychological functioning, cognitive functioning, and sleep are frequently experienced by individuals who have survived aneurysmal subarachnoid haemorrhage (aSAH). Exercise has been shown to improve these domains; to date, it has never been explored in patients following aSAH. The aim of this exploratory study is to compare the effects of an exercise programme in this population with another patient group, and a group of healthy controls. Methods: The present study explored the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 76 publications
0
56
0
Order By: Relevance
“…One hundred and six full texts were retrieved for detailed evaluation, of which 51 studies were excluded ( Figure 1). Fifty-five studies covering 6,327 patients (range, 40 to 1,181) in 47 cohorts (data from five cohorts were used in 13 publications [12][13][14][15][16][17][18][19][20][21][22][23][24] ) met the inclusion criteria ( Table 1). The majority of studies (46 of 55) included more female than men.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and six full texts were retrieved for detailed evaluation, of which 51 studies were excluded ( Figure 1). Fifty-five studies covering 6,327 patients (range, 40 to 1,181) in 47 cohorts (data from five cohorts were used in 13 publications [12][13][14][15][16][17][18][19][20][21][22][23][24] ) met the inclusion criteria ( Table 1). The majority of studies (46 of 55) included more female than men.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-one of 55 studies (93%) used one of the following screening or rating scales to ascertain the presence of depression: Hospital Anxiety Depression Scale (HADS), 18,19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Beck Depression Inventory (BDI), [12][13][14][15][16][17][18][19][20][21][40][41][42][43][44][45][46][47][48][49][50][51] Center for Epidemiologic Studies Depression (CESD), [22][23][24]52,53 Montgomery Åsberg Depression Rating Scale (MADRS), 54,55 Geriatric Depression Scale (GDS), 56,57 International Classification of Diseases...…”
Section: Resultsmentioning
confidence: 99%
“…The practice of regular physical exercise has beneficial effects for the integral health of the human being, in the physical sphere (Comin et al, 2018;Liu et al, 2018;Foright et al, 2018;Wiklund, 2016), mental (Colledge et al, 2018;Alonso-Patiño et al, 2013;Revnic et al, 2013) and socio-affective (Baillot et al, 2018;Rammant et al, 2017;Womble et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that, three months after aSAH, patients had significant functional limitations in terms of body movement, cognition, and emotion; these functional limitations, especially cognitive impairment, significantly affected the patients' activities of daily living at discharge and the probability of returning to work [2] [3] [10] [11] [12]. Many researchers have emphasized the importance of early and comprehensive professional rehabilitation, which can improve patients' quality of life [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…rehabilitation can improve depression, cognition, and language-learning ability[13] [14] [16] [17] [37]. However, there are few studies on rehabilitation in the convalescent period.…”
mentioning
confidence: 99%